1969
DOI: 10.1039/j19690001742
|View full text |Cite
|
Sign up to set email alerts
|

Azomethine derivatives. Part IX. Preparation of dialkylideneammonium salts via diarylketiminodiphenylmethyl chlorides

Abstract: WE here describe some salts containing a new class of cation, the dialkylideneammonium cation [R,C:N:CR,] +, which is isoelectronic with and apparently isostructural with allenes R,C:C:CR,.Salts of the cations [Ph2C:N:CPh2]+ and [P-tolyl,-C:N:CPh,]+ were prepared in order to study further the interesting relationship that exists between unsaturated organic compounds and cations formally derived from them by replacing a multiply bonded carbon atom by a positively charged nitrogen, e.g., compare alkynes RCiCR wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Two methylene planes are perpendicular to each other. The obtained bond length and angle are in reasonable agreement with those Böttger et al reported in 1997 at the B3LYP/6-31+G* level. In the product (see Scheme and Table S1), the ring atoms and the methylene group attached to N 1 are on the same plane, while the hydrogen atoms are distributed zygomorphically.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Two methylene planes are perpendicular to each other. The obtained bond length and angle are in reasonable agreement with those Böttger et al reported in 1997 at the B3LYP/6-31+G* level. In the product (see Scheme and Table S1), the ring atoms and the methylene group attached to N 1 are on the same plane, while the hydrogen atoms are distributed zygomorphically.…”
Section: Resultssupporting
confidence: 91%
“…In the past couple decades, [2 + 2] cycloaddition reactions of ketenes, ketenimines, allenes, and keteniminium cations have been extensively studied theoretically and experimentally. , In our previous paper, it was realized that the mechanism of cycloaddition reaction involving keteniminium cation is quite complicated, and thus it presents a great challenge for theoretical chemists. The 2-azoniaallene cation, a class of heterocumulenes, greatly interested chemists since the first 2-azoniaallene salts were prepared in 1969 by Samuel and Wade . During the past couple of decades, Würthwein et al developed a series of experimental and theoretical investigation for the synthesis, structure property, and chemical reactivity of 2-azoniaallene salts.…”
Section: Introductionmentioning
confidence: 99%
“…1,1-Elimination. Under suitable alkylation conditions, diaryl ketimines undergo reaction to form N -substituted imines; benzophenone imine 12i reacts with α-chlorobenzylmethyl ether and dichlorodiphenylmethane to form the N -substituted imines, N -(diphenylmethylene)-α-methoxybenzylamine ( 10 ) 15 and diphenylketiminodiphenylmethyl chloride ( 11 ), respectively. However, when the condensation is carried out with benzophenone imine 12i and α,α-dichlorotoluene 13 under a wide variety of experimental conditions, we have found that the expected chloride product 14 could not be isolated (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The preferred structural type of the cation depends very sensitively on the respective substitution pattern. Thus, electron donor groups favor the geometry 2 , whereas aliphatic substituents and aryl groups seem to shift the valence isomeric equilibrium toward the side of the 2-azaallenium geometry 1 . Due to their interesting structural and reactive properties both classes of compounds have been subject of intense experimental, spectroscopic, and theoretical investigations. …”
mentioning
confidence: 99%
“…Several routes for the synthesis of 2-azapropenylium salts have been disclosed. In contrast to the less reactive 2-azaallylium salts 2·X - , which may be isolated as chlorides or iodides, e.g., due to their higher reactivity the 2-azaallenium salts 1·X - require nonnucleophilic counterions for their isolation. In the past, mainly hexachloroantimonates have been used, although the oxidative (chlorinating) properties make this counterion not best suited for synthetic purposes.…”
mentioning
confidence: 99%